From carbonate platform to euxinic sea – the collapse of an Early/Middle Devonian reef, Cantabrian Mountains (Spain) - Loevezijn, Gerard B.S. van; Raven, J.G.M. (Geologos, 2017)
The Santa Lucía Formation represents the major phase in Devonian reef development of the Cantabrian Zone (Cantabrian Mountains, northwest Spain). In the present study the transition from the carbonate platform deposits of the Santa Lucía Formation to the overlying euxinic basinal deposits of the Huergas Formation is described. These transitional strata are connected to the Basal Choteč Event and represent a condensed sedimentation of micritic dark-grey and black limestones with an upward increase of dark shale intercalations with iron mineralisation surfaces and storm-induced brachiopod coquinas. The transitional beds are grouped into a new unit, the Cabornera Bed, which consists of limestone, limestone-shale and shale facies associations, representing a sediment-starved euxinic offshore area just below the storm wave base. Four stages in reef decline can be recognised: a reef stage, an oxygen-depleted, nutrient-rich stage, a siliciclastic-influx stage and a pelagic-siliciclastic stage. Additional geochemical and geophysical investigations are needed to verify the results presented herein.